2018
DOI: 10.1007/s10973-018-7311-y
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on infrared thermal imaging of cross-country skiers and swimmers subjected to endurance exercise

Abstract: This study was focused on the thermal mapping of skin over the selected muscle zones in two groups of elite athletes fully engaged in completely other sports performing about an hour running effort at individual AT intensity. Two groups of elite male athletes, a group of cross-country skiers (CS; N = 6) and a group of elite endurance swimmers (SW; N = 4), were investigated. Thermal images of sportsmen' body at front and from the rear were recorded before and about 1-2 min after exercise test using camera Flir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The assessment of spasticity revealed functional improvement in gait patterns and better functional activity as measured on subjective scales. Functional improvement can be visible on thermography possibly due to improvement in thermoregulatory processes following better blood flow and heat production as it has been shown that exercises improve efficiency of thermoregulatory processes [27,28]. The results of thermography were interesting, as well.…”
Section: Discussionmentioning
confidence: 95%
“…The assessment of spasticity revealed functional improvement in gait patterns and better functional activity as measured on subjective scales. Functional improvement can be visible on thermography possibly due to improvement in thermoregulatory processes following better blood flow and heat production as it has been shown that exercises improve efficiency of thermoregulatory processes [27,28]. The results of thermography were interesting, as well.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, from an image with the pixels representing different temperature values of the surface under study, IRT is a technique with a wide range of applications [26]: (1) civil engineering and buildings [1,15,[17][18][19]22], (2) IRT applied to different types of material [22,[27][28][29][30][31][32][33], (3) industrial applications [34][35][36], (4) environment [37][38][39] and (5) biomedical applications [40][41][42][43]. In the following subsection, a brief review with regard to the most recent IRT works that detect moisture areas affecting the surfaces of different construction materials is described.…”
Section: Bilateral Filtering Technique Applicationmentioning
confidence: 99%
“…Sweating is the main thermoregulatory response by which heat balance is maintained after a rise in body temperature during exercise-induced heat load. Evaporation of sweat from the skin surface has a cooling effect because evaporation is an endothermic process [20]. It is important to consider other factors that could influence differences in skin temperature between body regions [21].…”
Section: Resultsmentioning
confidence: 99%